The Production Of Ferronickel By The Rotary Kiln-Electric Furnace Process - Abraham A. Dor; Hans Skretting (Society for Mining, Metallurgy & Exploration, 1979)
This paper briefly reviews the historical development of the Rotary Kiln-Electric Furnace Process, which was first applied commercially to the treatment of qarnieritic ores in New Caledonia in the mid-fifties. It describes various technological improvements introduced, since, in industrial plants or developed in pilot facilities where a wide variety of nickel oxide ores has been treated success- fully over the years. Major categories of ores are characterized. The effect of their physical and chemical properties on their performance in the electric furnace is discussed. The relationships between ore composition, ferronickel grade and slag composition are analyzed and their effect on slag and metal tapping temperatures, nickel recovery, and electrode voltage are discussed.